Front view of the Vishnu Temple behind the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The front view (east) of the Vishnu Temple behind the Sitaleshwar Temple shows the temple standing on a platform. The doorframe of the garbhagriha (sanctum sanctorum) is panchashakha (five vertical bands). At the threshold, figures of river goddesses, dvarapalas (door guardians) and Kubera are depicted. The upper portions of the shakhas (vertical bands) are intricately carved with a variety of motifs and designs.